Identifying Safety Risk Sources in Bridges Construction: A Literature Review - Chusnia, Chizanatul; Wibawa, M. Rendy; Saputra, Pungky Dharma (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
The construction sector, particularly bridge construction, plays a vital role in the development of national infrastructure but also involves significant safety risks that may lead to various losses. To address these risks, effective risk management is required to identify potential hazards and prevent workplace accidents. This study aims to identify the sources of safety risks in bridge construction projects through a systematic literature review. A total of 100 relevant studies were collected and analyzed using the PRISMA approach, while VOS viewer was employed to map and visualize the relationships between risk factors. The findings indicate that six main sources of risk can occur in bridge construction projects, with human-related risks being the most frequent, followed by environmental and managerial factors. These results highlight the importance of systematically identifying safety risk sources to strengthen preventive measures and reduce the likelihood of accidents in construction projects. This study relies exclusively on secondary data derived from published literature, which may restrict its ability to comprehensively represent context-specific, dynamic, or emerging safety risks encountered in actual bridge construction practices. Future research should incorporate empirical investigations, such as field observations, surveys, or in-depth case studies, to validate the identified risk sources and to develop more robust, context-sensitive risk management frameworks for bridge construction projects.